Pengaruh Work Engagement terhadap Kinerja Karyawan melalui Komitmen Organisasi (Studi di Hotel Borobudur Jakarta) - Melianto Sandi; Meylani Tuti (Human Capital Development, 2022)
The purpose of this study was to determine the effect of work engagement on performance through organizational commitment. The research method used is Partial Least Square (PLS) using SmartPLS software. The sample in this research is the employees of Hotel Borobudur Jakarta with a total of 250 samples. Research data obtained from the distribution of questionnaires. The results of the study state that there is a positive and significant effect between work engagement on organizational commitment, work engagement has a positive and significant effect on performance, and organizational commitment has a positive and significant effect on performance.